Anxiety and depression during Covid-19 in elite rugby players: The role of mindfulness skills - Myall, K; Kuyken, W; Montero Marin, J (University of Oxford, 2021)
Data was collected to asses the prevalence of anxiety and depression in elite rugby players during the early stages of the covid-19 pandemic